Regulación de la desinformación digital: un estudio sociojurídico sobre las fake news y salud en el caso brasileño A socio-legal study on medical fake news in the Brazilian case = Regulation of digital misinformation : a socio-legal study on medical fake news in the Brazilian case - Barros, Marco Antonio Loschiavo Leme de (Oñati Socio-Legal Series, 2024)
The purpose of this paper is to present a socio-legal approach, mainly based on social systems theory, to the problem of mass disinformation through digital networks and platforms. To this end, the paper analyses fake news as a phenomenon emerging from a structural transformation in the means of communication dissemination, and then focuses on the case of Brazilian regulation on the subject. The guiding hypothesis of the research is that it is possible to identify a package of regulatory learning strategies by the legal system. The text specifically addresses the case of fake news on the subject of health. It notes that, in this field of medical fake news, there is a lack of proposals capable of combining forms of prevention and not only repression of damage.